Patterns of Food Consumption and Production of Mountainous Community in Sinjai District, South Sulawesi Province, Indonesia - Ahfandi Ahmad; Rahmadanih Rahmadanih; M. Saleh S. Ali (International Journal of Agriculture System, 2017)
Food availability of one area affects its community food consumption patterns. The area will use its natural resources to satisfy all needs of its society. This study aimed to explain the patterns of consumption and production of food in a mountainous area. This research is a descriptive study using both qualitative and quantitative approaches. In qualitative approach, the data obtained by indepth-interview and Focus Group Discussion (FGD), whereas quantitative data obtained through household surveys of 40 households as samples. Field data collection is done systematically through questionnaires and interviews. There are two data sources namely primary data and secondary data. Primary data were obtained from people in the local area either as informants selected using snowball techniqueor respondents selected purposively. Furthermore, the secondary data were obtained from the literature that correlates with research areas. The result shows that the pattern of food production in the mountainous region is divided into two types based on the land used that is wetland and dry land. The wetland is used by mountainous community to produce food such as rice and corn with a frequency of twice a year. As for the dry land, it is cultivated to produce vegetables that are produced throughout the year as daily necessities. The pattern of consumption in the community correlates with the amount, type and consumptive frequency of the food. In general, people in mountainous areas still consume rice as a staple food by eating vegetables and fish as complementary with a frequency of 2-3 times a day. This is because the access is still relatively easy to obtain these foods.